2021
DOI: 10.1093/trstmh/trab152
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the drugs used in migrant patients with severe acute respiratory syndrome coronavirus 2 and the development of symptomatic strongyloidiasis

Abstract: Background The use of dexamethasone in patients infected with Strongyloides stercoralis can cause severe complications. It is necessary to investigate the relationship between coronavirus disease 2019 (COVID-19) and strongyloidiasis infection. Methods A retrospective, longitudinal, descriptive study was undertaken to review all patients admitted with a diagnosis of COVID-19 infection at the Complejo Asistencial Universitario … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(44 citation statements)
references
References 15 publications
0
44
0
Order By: Relevance
“…Table 1 describes the main characteristics of two observational studies from the scoping review. 12,13 Overall, these two studies were observational studies without comparative groups to evaluate the characteristics of strongyloidiasis in COVID-19, specifically the effect of drugs used in COVID-19 on the evolution of strongyloidiasis and the current situation regarding diagnostic and treatment protocols for strongyloidiasis in COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 describes the main characteristics of two observational studies from the scoping review. 12,13 Overall, these two studies were observational studies without comparative groups to evaluate the characteristics of strongyloidiasis in COVID-19, specifically the effect of drugs used in COVID-19 on the evolution of strongyloidiasis and the current situation regarding diagnostic and treatment protocols for strongyloidiasis in COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Lorenzo et al 12 conducted a longitudinal study by reviewing patients diagnosed with COVID-19 from a tertiary care hospital in central-western Spain. Although their sample size was small (N 5 86), they identified seven patients with strongyloidiasis; of the seven, three received dexamethasone, and none received tocilizumab.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, although 885 of the total patient population born outside the U.S. were noted to have eosinophilia, only 356 patients (40.2%) underwent serologic testing for Strongyloides, highlighting the lack of healthcare provider awareness of this condition in low endemicity settings. A similar study conducted in Spain on 2567 patients with COVID-19 identified 86 patients from geographic areas considered endemic for Strongyloides, and identified 7 patients (8%) with Strongyloides infection based on serology (1 from Africa and 6 from Latin America) [ 29 ]. All of these patients survived with good outcomes and none required ICU care.…”
Section: Screeningmentioning
confidence: 99%
“…The full-text articles were then assessed for eligibility, which left 17 studies to extract data from. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] A PRISMA flow diagram was created to show the numbers of publications identified, included and excluded, and the criteria for exclusion (Figure 1). According to the JBI assessment tool for case-report studies, 14 (82.3%) studies were classified as low risk of bias; two studies 38,45 had a moderate risk of bias and one 47 a high risk of bias (Table 1 and Table S1).…”
Section: Overview Of Studiesmentioning
confidence: 99%